PENGEMBANGAN BAHAN AJAR ENGLISH FOR SPECIFIC PURPOSE BERBASIS TIK - Muhammad Yaumi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
This research is about the development of ICT-based English instructional mate-rials of English for Specific Purpose. The purpose of this study is to determine the type of instructional materials used in English language instruction, develop Eng-lish for Specific Purpose materials that integrate ICT, and assess the effectiveness of instruction by using ICT-based instructional materials as well as the traditional instruction. The method of research was a research and development. The met-hod of data collection were observation, interviews, study the document, port-folio, and tests. The technique of data analysis in this study used mixed method. The Results showed that ESP materials used in UIN Alauddin looked traditional and they were focused more in using textbook, white board, and face to face in-teraction. ICT based instruction has been developed systematically and revised based on recommendation, and the use of ICT based instruction is more effective than the one with printed materials.